Electrode and lithium battery comprising same
By arranging the electrode current collector with a porous structure in the electrode active material layer of the lithium battery and manufacturing the dry electrode by dry method, the dependence problem on organic solvents in the prior art is solved, and a lithium battery with high energy density and low internal resistance is achieved.
Patent Information
- Application Number
- CN202411483517.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-27
- Filing Date
- 2024-10-23
- Publication Date
- 2025-04-29
AI Technical Summary
Existing lithium batteries may use excessive organic solvents during the manufacturing process, resulting in environmental pollution and waste of resources, while it is difficult to achieve the goals of high energy density and miniaturization.
The dry electrode is manufactured by a dry method, by arranging two or more electrode current collectors of porous structures in the electrode active material layer, the dependence on the organic solvent is reduced and the conductivity of the electrode is improved.
The electrode manufacturing without solvents or low solvents is achieved, which reduces internal resistance, improves the energy density and fast charging performance of lithium batteries, and reduces environmental pollution.
Smart Images

Figure CN119905510A_ABST
Abstract
Description
[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2023-0145275 filed in the Korean Intellectual Property Office on October 27, 2023, the entire contents of which are incorporated herein by reference. Technical Field
[0002] Embodiments of the present disclosure relate to an electrode and a lithium battery including the electrode. Background Art
[0003] In order to meet the characteristics of miniaturization and relatively high performance of various devices, in addition to the reduced size and weight reduction of lithium batteries, relatively high energy density is also important. In this regard, relatively high-capacity lithium batteries are important.
[0004] Electrodes manufactured from a slurry including a solvent (eg, an organic solvent) may use an excess amount of the solvent during manufacture of the electrode. Therefore, dry processes that do not include (eg, exclude) the use of such a solvent (eg, an organic solvent) are being studied or pursued. Summary of the invention
[0005] An aspect of one or more embodiments of the present disclosure relates to a dry electrode including two or more electrode current collectors, the electrode current collectors including (eg, comprising) a porous structure.
[0006] An aspect of one or more embodiments of the present disclosure relates to a lithium battery including the above-mentioned electrode.
[0007] Additional aspects will be set forth in part in the description which follows and, in part, will be obvious from the description, or may be learned by practice of the presented embodiments of the disclosure.
[0008] According to one or more embodiments of the present disclosure, an electrode includes: an electrode active material layer; and two or more electrode current collectors arranged along the thickness direction within the electrode active material layer, wherein the areas of the two or more electrode current collectors overlapping with the electrode active material layer in the thickness direction include (e.g., contain) a porous structure.
[0009] According to one or more embodiments of the present disclosure, an electrode includes: an electrode active material layer; and two or more electrode current collectors, which are arranged along the thickness direction within the electrode active material layer, wherein the two or more electrode current collectors include: an upper electrode current collector, which is adjacent to the top surface of the electrode active material layer; and a lower electrode current collector, which is adjacent to the bottom surface of the electrode active material layer, wherein the electrode active material layer includes: an inner electrode active material layer, between the upper electrode current collector and the lower electrode current collector; and an outer electrode active material layer, outside the upper electrode current collector and the lower electrode current collector, and wherein the two or more electrode current collectors include a porous structure.
[0010] According to one or more embodiments of the present disclosure, a lithium battery includes a first electrode, a second electrode, and an electrolyte, wherein the first electrode, the second electrode, and / or any suitable combination thereof may be (eg, may both be) the above electrodes. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] The above and other aspects, features and / or principles of certain embodiments of the present disclosure will become more apparent through the following description in conjunction with the accompanying drawings, in which: Figure 1 is a schematic cross-sectional view showing a stacked state of electrodes according to one or more embodiments of the present disclosure; Figure 2 is a schematic cross-sectional view showing a stacked state of electrodes according to one or more embodiments of the present disclosure; Figure 3 is a schematic cross-sectional view showing a stacked state of electrodes according to a comparative example; Figure 4 is a scanning electron microscope image of a cross section of a dry electrode film containing a fibrillated dry binder; Figure 5 is a schematic perspective view showing a method of manufacturing a dry electrode film according to one or more embodiments of the present disclosure; Figure 6 is a schematic exploded perspective view of a lithium battery according to one or more embodiments of the present disclosure; Figure 7 is a schematic exploded perspective view of a lithium battery according to one or more embodiments of the present disclosure; and Figure 8 is a schematic exploded perspective view of a lithium battery according to one or more embodiments of the present disclosure. DETAILED DESCRIPTION
[0012] The present disclosure can be modified in many alternative forms, and therefore specific embodiments will be shown in the drawings and described in more detail. However, it should be understood that this is not intended to limit the present disclosure to the particular form disclosed, but is intended to cover all modifications, equivalents and substitutes falling within the spirit and scope of the present disclosure.
[0013] Now will refer to embodiment in more detail, the example of embodiment is shown in the accompanying drawings, wherein the same reference numerals always refer to the same elements, and its repeated description may not be provided. In this regard, the embodiment provided may have different forms, and should not be construed as being limited to the description set forth herein. Therefore, only one or more embodiments are described in more detail with reference to the accompanying drawings to explain the various aspects of this specification. These embodiments are provided as examples so that the present disclosure will be thorough and complete, and the aspects and features of the present disclosure will be fully conveyed to those skilled in the art. Therefore, it may not be described that it is not necessary for those of ordinary skill in the art to fully understand the aspects and features of the present disclosure, process, element and technology.
[0014] As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items. Unless otherwise apparent through disclosure, expressions such as "at least one of...", "a plurality of", "one of..." and other prepositional phrases, when preceding / following a list of elements, should be understood to include disjuncts if written as a conjunction list, and vice versa. For example, the expression "at least one of a, b or c", "at least one of a, b and / or c", "one selected from the group consisting of a, b and c", "at least one selected from a, b and c", "at least one among a, b and c", "one among a, b and c", "at least one from a to c" means only a, only b, only c, both a and b, both a and c, both b and c, all of a, b and c, or variations thereof.
[0015] Various embodiments are shown in the accompanying drawings. However, the present disclosure may be implemented in various other forms and should not be construed as limited to the one or more embodiments set forth herein.
[0016] Although the terms "first", "second", "third", etc. may be used herein to describe various elements, components, regions, layers and / or parts, these elements, components, regions, layers and / or parts should not be limited by these terms. These terms are only used to distinguish one element, component, region, layer or part from another element, component, region, layer or part. Therefore, without departing from the spirit and scope of the present disclosure, the first element, first component, first region, first layer or first part described below may be referred to as the second element, second component, second region, second layer or second part.
[0017] The terms used herein are only used for the purpose of describing specific embodiments and are not intended to limit the present disclosure. As used herein, the singular forms "a", "one", and "the" are also intended to include the plural forms unless the context clearly indicates otherwise. "At least one" should not be interpreted as being limited to the singular.
[0018] It will also be understood that when the terms "comprises," "including," "has," and "contains" and variations thereof are used in this specification, they indicate the presence of stated features, regions, wholes, steps, operations, elements, ingredients, and / or components, but do not preclude the presence or addition of one or more other features, regions, wholes, steps, operations, elements, ingredients, components, and / or groups thereof.
[0019] For ease of explanation, spatially relative terms such as "under", "below", "below", "below", "above", "upper", etc. may be used herein to describe the relationship of one element or feature to another element or features as shown in the figure. It will be understood that, in addition to the orientation depicted in the figure, the spatially relative terms are intended to cover different orientations of the device in use or in operation. For example, if the device in the figure is turned over, the elements described as "below" or "below" or "below" other elements or features will then be oriented as "above" other elements or features. Therefore, the example terms "below" and "below" can cover both above and below orientations. The device can be oriented otherwise (e.g., rotated 90 degrees or in other orientations), and the spatially relative descriptors used herein should be interpreted accordingly.
[0020] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the present disclosure belongs. It will also be understood that terms (such as those defined in commonly used dictionaries) should be interpreted as having a meaning consistent with their meaning in the context of the relevant art and / or the present disclosure, and should not be interpreted in an idealized or overly formal sense, unless expressly defined as such herein.
[0021] One or more embodiments are described herein with reference to cross-sectional views of schematic diagrams as idealized implementation examples. As described above, modifications of the shapes shown may occur, for example, as a result of manufacturing techniques and / or tolerances. Therefore, the embodiments described herein should not be interpreted as being limited to the specific shapes of the regions as shown herein, but should include shape changes caused by, for example, manufacturing. For example, a region shown or described as flat may typically have rough and / or nonlinear features. In addition, angles shown sharply may be rounded (rounded). Therefore, the regions shown in the drawings are schematic in nature, and the shapes are not intended to depict the exact shape of the regions, and are not intended to limit the spirit or scope of the claims.
[0022] In the drawings, the thickness of layers and regions may be exaggerated or reduced for clarity of description. Throughout the specification, if a component such as a layer, film, region, or plate is described as being "above," "on," "connected to," or "bonded to" another component, the component may be directly above, directly on, directly connected to, or directly bonded to the other component, or one or more intervening components may be present. In addition, it will be understood that when a component is referred to as being "between" two components, the component may be the only component between the two components, or one or more intervening components may also be present.
[0023] As used herein, the term "dry electrode" or "dry electrode film" may refer to an electrode or electrode film that does not include a solvent or does not intentionally use a solvent in the electrode manufacturing process. The solvent may include a process solvent, a process solvent residue, a process solvent impurity, etc.
[0024] As used herein, if the particles are spherical, the "particle size" of the particles means the average diameter, and if the particles are non-spherical, the "particle size" of the particles means the average major axis length. The particle size can be measured using a particle size analyzer (PSA). The "particle size" can be, for example, the average particle size. The "average particle size" can be, for example, D50 as a median particle size, which refers to the average diameter (or size) of particles whose cumulative volume corresponds to 50 vol% in a particle size distribution (e.g., cumulative distribution), and refers to the value of the particle size corresponding to 50% from the smallest particle when the total number of particles in the distribution curve accumulated in the order from the smallest particle size to the largest particle size is 100%.
[0025] In the present disclosure, "not including one or any "component"", "excluding one or any "component"", "containing no component" and the like means that the "component" is not added, selected or used as a component in the composition / structure, but due to other impurities and / or external factors, less than an appropriate amount of the "component" may still be included.
[0026] As used herein, "electrode active material" refers to an electrode material that is capable of undergoing lithiation and delithiation.
[0027] As used herein, "positive electrode active material" refers to a positive electrode material that is capable of undergoing lithiation and delithiation.
[0028] As used herein, "negative electrode active material" refers to a negative electrode material that is capable of undergoing lithiation and delithiation.
[0029] As used herein, the terms "lithiation" and "lithiating" refer to the process of adding lithium to an electrode active material.
[0030] As used herein, the terms "delithiation" and "delithiation" refer to the process of releasing lithium from an electrode active material.
[0031] As used herein, "charging" and "charging" refer to the process of providing electrochemical energy to a battery.
[0032] As used herein, "discharge" and "discharging" refer to the process of removing electrochemical energy from a battery.
[0033] As used herein, "positive electrode" and "cathode" refer to the electrode that undergoes electrochemical reduction and lithiation during the discharge process.
[0034] As used herein, "negative electrode" and "anode" refer to the electrode at which electrochemical oxidation and delithiation occur during the discharge process.
[0035] As used herein, the terms "fibrillate" and "fibrillation" refer to the process of converting particles of a substance (eg, by grinding or comminuting) into fibrous forms of the substance (ie, fibrils) having a higher aspect ratio than the particles.
[0036] Although specific embodiments have been described, applicants or those skilled in the art may recognize that there may be alternatives, modifications, variations, improvements, and substantial equivalents that are not currently contemplated or foreseen. Therefore, the appended claims that may be submitted and amended are intended to cover all such alternatives, modifications, variations, improvements, and substantial equivalents.
[0037] Hereinafter, an electrode and a lithium battery including the same according to one or more embodiments will be described in more detail.
[0038] Figure 1 is a schematic cross-sectional view showing a stacked state of electrodes according to one or more embodiments of the present disclosure. Figure 2 is a schematic cross-sectional view showing a stacked state of electrodes according to one or more embodiments of the present disclosure. Figure 3 is a schematic cross-sectional view showing a stacked state of electrodes according to a comparative example.
[0039] Reference Figures 1 to 3 According to one or more embodiments, the electrode 100 may include: an electrode active material layer 120; and two or more electrode current collectors 110, which are arranged with each other along a thickness direction (e.g., a thickness direction normal to a plan view of the electrode 100) in the electrode active material layer 120 (e.g., an upper electrode current collector 111 and a lower electrode current collector 112 are arranged with each other along a thickness direction (e.g., a thickness direction normal to a plan view of the electrode 100) in the electrode active material layer 120), wherein the two or more electrode current collectors 110 may include The upper electrode current collector 111 is adjacent to the top surface A of the active material layer 120, and the lower electrode current collector 112 is adjacent to the bottom surface B of the electrode active material layer 120. The electrode active material layer 120 may include an inner electrode active material layer 122 arranged between the upper electrode current collector 111 and the lower electrode current collector 112, and an outer electrode active material layer 121 arranged outside the upper electrode current collector 111 and the lower electrode current collector 112, and the area in the electrode current collector 110 overlapping with the electrode active material layer 120 in the thickness direction may include a porous structure.
[0040] Reference Figure 3 , the electrode of the prior art includes only one electrode current collector, so electrons may easily move from the electrode active material adjacent to the electrode current collector among the electrode active materials contained in the electrode active material layer to the electrode current collector, but electrons may not easily move from the electrode active material away from the electrode current collector to the electrode current collector. Therefore, there is a limitation that the internal resistance of the electrode may increase. In the embodiments of the present disclosure, referring to Figure 1 and Figure 2 , the electrode 100 includes two or more electrode current collectors 110 including a porous structure inside the electrode active material layer 120, which can make the electrode active material adjacent to another electrode current collector 110 even when (for example, when) the electrode active material is far away from any one electrode current collector 110, so the distance between the electrode active material and the electrode current collector 110 (hereinafter, when referring to "electrode current collector 110", it refers to any one or at least one of the electrode current collectors 110) can be reduced. Therefore, during the charging and discharging of the lithium battery including the electrode 100, the travel distance of the electrons from the electrode active material to the electrode current collector 110 is reduced, so the internal resistance of the electrode 100 can be reduced. Therefore, the lithium battery including the electrode 100 can have a reduced internal resistance, so the overvoltage and internal temperature increase of the battery during fast charging can be suppressed or reduced.
[0041] For example, the outer electrode active material layer 121 may include a first outer active material layer disposed on the top surface of the upper electrode current collector 111 and a second outer active material layer disposed on the bottom surface of the lower electrode current collector 112 .
[0042] According to one or more embodiments, the thickness of the inner electrode active material layer 122 may be greater than the thickness of the outer electrode active material layer 121. For example, the thickness of the inner electrode active material layer 122 may be greater than the thickness of the first outer electrode active material layer and / or the second outer electrode active material layer.
[0043] According to one or more embodiments, the inner electrode active material layer 122 may have a thickness of about 10 micrometers (μm) to about 190 μm, the outer electrode active material layer 121 may have a thickness of about 10 μm to about 190 μm, and the electrode active material layer 120 may have a total thickness of about 20 μm to about 380 μm. For example, the inner electrode active material layer 122 may have a thickness of about 50 μm to about 150 μm, the outer electrode active material layer 121 may have a thickness of about 20 μm to about 100 μm, and the electrode active material layer 120 may have a total thickness of about 100 μm to about 300 μm.
[0044] For example, the first outer electrode active material layer and the second outer electrode active material layer may each have a thickness of about 10 μm to about 190 μm. For example, the first outer electrode active material layer and the second outer electrode active material layer may each have a thickness of about 20 μm to about 100 μm. For example, the thickness of the electrode active material layer 120 may refer to the sum of the thicknesses of the first outer electrode active material layer, the second outer electrode active material layer, and the inner electrode active material layer 122.
[0045] According to one or more embodiments, the electrode active material layer 120 may be a dry electrode film, wherein the dry electrode film may be a free-standing film and may not contain any residual processing solvent.
[0046] Figure 4 is a scanning electron microscope (SEM) image of a cross section of a dry electrode film according to one or more embodiments of the present disclosure. Figure 4 , the electrode active material layer 120 may include a dry binder fibrillated in a first direction. The first direction may be, for example Figure 4 The first direction may be an X-axis direction in the electrode 100 (eg, a direction parallel to a plan view of the electrode 100). For example, as described in more detail below, the first direction may be a machine direction MD.
[0047] Figure 5 is a schematic perspective view illustrating a method of manufacturing a dry electrode film according to one or more embodiments of the present disclosure.
[0048] Reference Figure 5 , the dry electrode film composition is processed into a dry electrode film by passing the dry electrode film composition between a pair of calendering rollers. The direction in which the dry electrode film moves while being formed is the processing direction MD of the dry electrode film. The first dry electrode active material composition can be stretched along the processing direction while passing through a pair of calendering rollers, so the first dry electrode active material layer 100a may include a first dry binder that is fibrillated in the processing direction. The width direction TD of the first dry electrode active material layer 100a may be a direction that intersects with the processing direction MD of the first dry electrode active material layer 100a.
[0049] According to one or more embodiments, the dry electrode film may include a dry electrode active material and a dry binder.
[0050] According to one or more embodiments, the dry electrode active material may include a positive electrode active material. According to one or more embodiments, the dry electrode active material may include a negative electrode active material.
[0051] For example, if the dry electrode film is a positive electrode film, the dry electrode active material may include a positive electrode active material.
[0052] For example, the positive electrode active material may be a lithium metal oxide, and any suitable material generally available and / or generally used in the art may be used without limitation.
[0053] For example, a composite oxide of lithium and one or more types (kinds) of metals including (e.g., selected from) cobalt, manganese, nickel and / or any suitable combination thereof may be used as the positive electrode active material, and examples thereof may be compounds represented by any one or more of the following: Li a A 1-b B b D2 (where 0.90≤a≤1, and 0≤b≤0.5); Li a E 1- b B b O 2-c D c (where 0.90≤a≤1, 0≤b≤0.5, and 0≤c≤0.05); LiE 2-b B b O 4-c D c (where 0≤b≤0.5 and 0≤c≤0.05); Li a Ni 1-b-c Co b B c D α(where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, and 0<α≤2); Li a Ni 1-b-c Co b B c O 2-α F α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni 1-b- c Co b B c O 2-α F2 (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni 1-b-c Mn b B c D α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, and 0<α≤2); Li a Ni 1-b-c Mn b B c O 2-α F α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni 1-b-c Mn b B c O 2-α F2 (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni b E c G d O2 (where 0.90≤a≤1, 0≤b≤0.9, 0≤c≤0.5, and 0.001≤d≤0.1); Li a Ni b Co c Mn d G e O2 (where 0.90≤a≤1, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, and 0.001≤e≤0.1); Li a NeG b O2 (where 0.90≤a≤1, and 0.001≤b≤0.1); Li a CoG b O2 (where 0.90≤a≤1, and 0.001≤b≤0.1); Lia MnG b O2 (where 0.90≤a≤1, and 0.001≤b≤0.1); Li a Mn b O4 (where 0.90≤a≤1, and 0.001≤b≤0.1); QO2; QS2; LiQS2; V2O5; LiV2O5; LiIO2; LiNiVO4; Li (3-f) J2(PO4)3(0≤f≤2);Li (3-f) Fe2(PO4)3 (0≤f≤2); and LiFePO4.
[0054] In the formulas representing these compounds, A is Ni, Co, Mn and / or any suitable combination thereof; B is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, rare earth elements and / or any suitable combination thereof; D is O, F, S, P and / or any suitable combination thereof; E is Co, Mn and / or any suitable combination thereof; F is F, S, P and / or any suitable combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V and / or any suitable combination thereof; Q is Ti, Mo, Mn and / or any suitable combination thereof; I is Cr, V, Fe, Sc, Y and / or any suitable combination thereof; and J is V, Cr, Mn, Co, Ni, Cu and / or any suitable combination thereof.
[0055] A compound to which a coating layer is added to the surface of the above-mentioned compound can be used, and / or any suitable mixture of the above-mentioned compound and the compound added with the coating layer can also be used. The coating layer added to the surface of the above-mentioned compound can include, for example, a coating element compound, such as an oxide or hydroxide of the coating element, an oxyhydroxide of the coating element, an oxygen-containing carbonate of the coating element, or a hydroxycarbonate of the coating element. The compound constituting the coating layer can be amorphous or crystalline. The coating layer element included in the coating layer can be Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr and / or any suitable mixture thereof. The method for forming (or setting) the coating layer can be selected within the range that does not adversely affect the physical properties of the positive electrode active material. The coating method can be, for example, a spraying method and / or an impregnation method, etc. A detailed description of the coating method will not be provided because it can generally be understood by those skilled in the art.
[0056] The positive electrode active material may be, for example, a composite positive electrode active material.
[0057] The composite positive electrode active material may include, for example: a core including a lithium transition metal oxide; and a shell arranged along the surface of the core, wherein the shell includes: aO b One or more first metal oxides represented by (where 0 < a ≤ 3 and 0 < b < 4, and if a is 1, 2, or 3, then b is not an integer); and graphene, wherein the first metal oxide is disposed in a graphene matrix, and M above is one or more metals from (for example, selected from) Groups 2 to 13, 15, and / or 16 of the periodic table, and the lithium transition metal oxide contains nickel, and the amount of nickel is 80 mol% or higher relative to the total moles of transition metals. A shell including the first metal oxide and graphene is disposed on the core of the composite positive electrode active material.
[0058] Due to agglomeration, it may be difficult to coat graphene uniformly (substantially uniformly) on the core. For example, the composite positive electrode active material can use a composite including a plurality of first metal oxides disposed in a graphene matrix, so that the shell is disposed uniformly (substantially uniformly) on the core while preventing or reducing the agglomeration of graphene. Therefore, by effectively blocking the contact between the core and the electrolyte solution, side reactions caused by the contact between the core and the electrolyte solution can be prevented or reduced. In one or more embodiments, the reduction of nickel ions (Ni 3+ →Ni 2 + ) and cation mixing caused by the electrolyte solution can be inhibited or reduced, so that the generation of a resistance layer such as a NiO phase can be inhibited or reduced. In one or more embodiments, the elution of nickel ions can also be inhibited or reduced. Because the shell including graphene is flexible, the volume change of the composite positive electrode active material during charging and discharging can be easily received, thereby inhibiting or reducing the occurrence of cracks inside the composite positive electrode active material. Because graphene has relatively high electron conductivity, the interfacial resistance between the composite positive electrode active material and the electrolyte solution can be reduced. Therefore, although a shell including graphene is introduced, the internal resistance of the lithium battery can be maintained or reduced.
[0059] In one or more embodiments, because the first metal oxide has voltage resistance, deterioration of the lithium transition metal oxide included in the core during charging and discharging at a relatively high voltage can be prevented or reduced. As a result, the cycle properties and relative high-temperature stability of a lithium battery including the composite positive electrode active material can be improved. The shell may include, for example, one type (or species) of the first metal oxide or two or more different types (species) of the first metal oxide. In the composite positive electrode active material, the lithium transition metal oxide may have a relatively high nickel content (e.g., amount) of about 80 mol% or more relative to the total molar amount of the transition metal, and the shell including the first metal oxide and graphene may be disposed on the core such that a relatively high discharge capacity and cycle properties can be provided in parallel (e.g., simultaneously). Therefore, the composite positive electrode active material having a relatively high nickel content (e.g., amount) of about 80 mol% or more can still provide excellent or suitable life properties while providing improved capacity as compared with the composite positive electrode active material having a relatively low nickel content (e.g., amount). The metal included in the first metal oxide may be, for example, one or more of Al, Nb, Mg, Sc, Ti, Zr, V, W, Mn, Fe, Co, Pd, Cu, Ag, Zn, Sb, and / or Se (e.g., one or more selected from among Al, Nb, Mg, Sc, Ti, Zr, V, W, Mn, Fe, Co, Pd, Cu, Ag, Zn, Sb, and / or Se).
[0060] The first metal oxide may be, for example, Al2O z (0 < z < 3), NbO x (0 < x < 2.5), MgO x (0 < x < 1), Sc2O z (0 < z < 3), TiO y (0 < y < 2), ZrO y (0 < y < 2), V2O z (0 < z < 3), WO y (0 < y < 2), MnO y (0 < y < 2), Fe2O z (0 < z < 3), Co3O w (0 < w < 4), PdO x (0 < x < 1), CuO x (0 < x < 1), AgO x (0 < x < 1), ZnO x (0 < x < 1), Sb2O z (0 < z < 3) and / or SeO y (0 < y < 2) or one or more of them (e.g., one or more selected from Al2O z(0 < z < 3), NbO x (0 < x < 2.5), MgO x (0 < x < 1), Sc2O z (0 < z < 3), TiO y (0 < y < 2), ZrO y (0 < y < 2), V2O z (0 < z < 3), WO y (0 < y < 2), MnO y (0 < y < 2), Fe2O z (0 < z < 3), Co3O w (0 < w < 4), PdO x (0 < x < 1), CuO x (0 < x < 1), AgO x (0 < x < 1), ZnO x (0 < x < 1), Sb2O z (0 < z < 3) and / or SeO y (0 < y < 2) or more of them). Since the first metal oxide as described above is arranged in the graphene matrix, the uniformity of the shell arranged on the core can be improved and the voltage resistance of the composite positive electrode active material can be further improved. For example, the shell may include Al2O x (0 < x < 3) as the first metal oxide. The shell may also include one or more types (species) of second metal oxides represented by the formula M a O c (0 < a ≤ 3 and 0 < c ≤ 4, if a is 1, 2 or 3, then c is an integer). The above M is one or more metals (for example, selected from) Groups 2 to 13, 15 and / or 16 of the periodic table. For example, the second metal oxide may include the same metal as the metal included in the first metal oxide, and the value of c / a as the ratio of c to a of the second metal oxide may be greater than the value of b / a as the ratio of b to a of the first metal oxide. For example, c / a > b / a. The second metal oxide may be (for example, may be selected from) for example Al2O3, NbO, NbO2, Nb2O5, MgO, Sc2O3, TiO2, ZrO2, V2O3, WO2, MnO2, Fe2O3, Co3O4, PdO, CuO, AgO, ZnO, Sb2O3 and / or SeO2. The first metal oxide is a reduction product of the second metal oxide. The first metal oxide is obtained by reducing part or all of the second metal oxide. Therefore, the first metal oxide may have an oxygen content (for example, amount) lower than that of the second metal oxide, and may have a higher metal oxidation number than the second metal oxide. For example, the shell may include Al2O as the first metal oxide x(0 < x < 3) and Al2O3 as the second metal oxide. In the composite positive electrode active material, for example, the transition metal including graphene in the shell and the lithium transition metal oxide in the core can be chemically bonded through chemical bonds. The carbon atoms (C) of the graphene included in the shell and the transition metal (Me) of the lithium transition metal oxide can be chemically bonded, for example, through a C-O-Me bond (e.g., a C-O-Ni bond) mediated by an oxygen atom. The graphene included in the shell and the lithium transition metal oxide included in the core can be chemically bonded through chemical bonds, so that the core and the shell can be a composite (e.g., can be compounded). Therefore, it is different from a simple physical mixture of graphene and lithium transition metal oxide. In one or more embodiments, the first metal oxide and graphene included in the shell can also be chemically bonded through chemical bonds. The chemical bond can be, for example, a covalent bond or an ionic bond. The covalent bond is a bond including at least one of, for example, an ester group, an ether group, a carbonyl group, an amide group, a carbonic anhydride group, and / or an acid anhydride group. The ionic bond is a bond including, for example, a carboxylate ion, an ammonium ion, and / or an acyl cation group, etc. The thickness of the shell can be, for example, about 1 nanometer (nm) to about 5 micrometers (μm), about 1 nm to about 1 μm, about 1 nm to about 500 nm, about 1 nm to about 200 nm, about 1 nm to about 100 nm, about 1 nm to about 90 nm, about 1 nm to about 80 nm, about 1 nm to about 70 nm, about 1 nm to about 60 nm, about 1 nm to about 50 nm, about 1 nm to about 40 nm, about 1 nm to about 30 nm, about 1 nm to about 20 nm, or about 1 nm to about 10 nm. Since the thickness of the shell falls within the above range, an increase in the internal resistance of the lithium battery including the composite positive electrode active material can be suppressed or reduced.
[0061] Relative to the total weight of the composite positive electrode active material, the amount of the composite included in the composite positive electrode active material may be about 3wt% or less, about 2wt% or less, about 1wt% or less, about 0.5wt% or less, or about 0.2wt% or less. Relative to the total weight of the composite positive electrode active material, the amount of the composite may be about 0.01wt% to about 3wt%, about 0.01wt% to about 1wt%, about 0.01wt% to about 0.7wt%, about 0.01wt% to about 0.6wt%, about 0.01wt% to about 0.5wt%, about 0.01wt% to about 0.2wt%, about 0.01wt% to about 0.1wt%, or about 0.03wt% to about 0.07wt%. Because the amount of the composite included in the composite positive electrode active material falls within the above range, the cycle properties of the lithium battery including the composite positive electrode active material can be further improved. The average particle size of one or more of the first metal oxide and / or the second metal oxide included in the composite (e.g., one or more selected from the first metal oxide and / or the second metal oxide included in the composite) (e.g., the average particle size of each of the particles of the first metal oxide and / or the second metal oxide) can be about 1 nm to about 1 μm, about 1 nm to about 500 nm, about 1 nm to about 200 nm, about 1 nm to about 100 nm, about 1 nm to about 70 nm, about 1 nm to about 50 nm, about 1 nm to about 30 nm, about 3 nm to about 30 nm, about 3 nm to about 25 nm, about 5 nm to about 25 nm, about 5 nm to about 20 nm, or about 7 nm to about 20 nm. Because the particle size of the first metal oxide and / or the second metal oxide falls within the above-mentioned nanoscale range, the first metal oxide and / or the second metal oxide can be more uniformly (substantially uniformly) distributed in the graphene matrix of the composite. Therefore, the above-mentioned composite can be uniformly (substantially uniformly) coated on the core without agglomeration, thereby forming (or setting) a shell. In one or more embodiments, because the particle size of the first metal oxide and / or the second metal oxide falls within the above range, the first metal oxide and / or the second metal oxide can be more uniformly (substantially uniformly) arranged on the core. Therefore, because the first metal oxide and / or the second metal oxide are uniformly (substantially uniformly) arranged on the core, the withstand voltage property can be more effectively exhibited. The average particle size of the first metal oxide and / or the second metal oxide can be measured by using, for example, a measuring device using a laser diffraction method or a dynamic light scattering method. If (for example, when) 50% of the cumulative volume is reached from the minimum particle size, the average particle size is the value of the median particle size (D50), and it can be measured, for example, using a laser scattering particle size analyzer (such as Horiba LA-920) and converting the data into volume.
[0062] The core included in the composite positive electrode active material includes, for example, a lithium transition metal oxide represented by one or more of Formula 1 to Formula 8: Formula 1 Li a Co x M y O 2-b A b In the above Formula 1, 1.0 ≤ a ≤ 1.2, 0 ≤ b ≤ 0.2, 0.9 ≤ x ≤ 1, 0 ≤ y ≤ 0.1, x + y = 1, M may be manganese (Mn), niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), boron (B), and / or any suitable combination thereof, and A may be fluorine (F), sulfur (S), chlorine (Cl), bromine (Br), and / or any suitable combination thereof.
[0063] Formula 2 Li a Ni x Co y M z O 2-b A b In the above Formula 2, 1.0 ≤ a ≤ 1.2, 0 ≤ b ≤ 0.2, 0.8 ≤ x < 1, 0 ≤ y ≤ 0.3, 0 < z ≤ 0.3, x + y + z = 1, M may be manganese (Mn), niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), boron (B), and / or any suitable combination thereof, and A may be F, S, Cl, Br, and / or any suitable combination thereof.
[0064] Formula 3 LiNi x Co y Mn z O2 Formula 4 LiNi x Co y Al z O2 In the above Formula 3 and Formula 4, 0.8 ≤ x ≤ 0.95, 0 ≤ y ≤ 0.2, 0 < z ≤ 0.2, and x + y + z = 1.
[0065] Formula 5 LiNi x Co y Mn z Al wO2 In the above formula 5, 0.8 ≤ x ≤ 0.95, 0 ≤ y ≤ 0.2, 0 < z ≤ 0.2, 0 < w ≤ 0.2, and x + y + z + w = 1.
[0066] Formula 6 Li a Ni x Mn y M’ z O 2-b A b In the above formula 6, 1.0 ≤ a ≤ 1.2, 0 ≤ b ≤ 0.2, 0 < x ≤ 0.3, 0.5 ≤ y < 1, 0 < z ≤ 0.3, and x + y + z = 1, M’ can be cobalt (Co), niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), boron (B) and / or any suitable combination thereof, and A can be F, S, Cl, Br and / or any suitable combination thereof.
[0067] Formula 7 Li a M1 x M2 y PO 4-b X b In the above formula 7, 0.90 ≤ a ≤ 1.1, 0 ≤ x ≤ 0.9, 0 ≤ y ≤ 0.5, 0.9 < x + y < 1.1, and 0 ≤ b ≤ 2, M1 can be chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zirconium (Zr) and / or any suitable combination thereof, M2 can be magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), titanium (Ti), zinc (Zn), boron (B), niobium (Nb), gallium (Ga), indium (In), molybdenum (Mo), tungsten (W), aluminum (Al), silicon (Si), chromium (Cr), vanadium (V), scandium (Sc), yttrium (Y) and / or any suitable combination thereof, and X can be O, F, S, P and / or any suitable combination thereof.
[0068] Formula 8 Li a M3 z PO4 In the above formula 8, 0.90 ≤ a ≤ 1.1, and 0.9 ≤ z ≤ 1.1, M3 can be chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zirconium (Zr) and / or any suitable combination thereof.
[0069] The amount of the positive electrode active material included in the dry electrode film can be, for example, about 80 wt% to about 98 wt%, or about 90 wt% to about 98 wt% relative to the total weight of the dry electrode film.
[0070] For example, if the dry electrode film is a negative electrode film, the dry electrode active material can include a negative electrode active material.
[0071] For example, the negative electrode active material can be any suitable negative electrode active material that is commonly available in the art and / or is commonly used as a negative electrode active material for a lithium battery. For example, it can include one or more selected from the group consisting of (e.g., selected from the group consisting of) lithium metal, a metal alloyable with lithium, a transition metal oxide, a non-transition metal oxide, and / or a carbonaceous material (e.g., composed of lithium metal, a metal alloyable with lithium, a transition metal oxide, a non-transition metal oxide, and / or a carbonaceous material). The metal alloyable with lithium can be, for example, Si, Sn, Al, Ge, Pb, Bi, Sb, a Si-Y alloy (where Y is an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a transition metal, a rare earth element, and / or any suitable combination thereof, but not Si), a Sn-Y alloy (where Y is an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a transition metal, a rare earth element, and / or any suitable combination thereof, but not Sn), etc. The element Y can be, for example, Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ti, Ge, P, As, Sb, Bi, S, Se, Te, Po, and / or any suitable combination thereof. The transition metal oxide can be, for example, lithium titanium oxide, vanadium oxide, lithium vanadium oxide, etc. The non-transition metal oxide can be, for example, SnO x (0 < x ≤ 2), SiO x (0 < x ≤ 2), etc. The carbonaceous material can be, for example, crystalline carbon, amorphous carbon, and / or any suitable mixture thereof. The crystalline carbon can be, for example, graphite, such as natural graphite or artificial graphite that is amorphous, plate-like (e.g., in the form of a plate), flaky, spherical, or fibrous. The amorphous carbon can be, for example, soft carbon (low-temperature fired carbon) or hard carbon, mesophase pitch carbide, fired coke, etc.
[0072] The amount of the negative electrode active material included in the dry electrode film may be, for example, about 80 wt % to about 98 wt %, or about 90 wt % to about 98 wt %, relative to the total weight of the dry electrode film.
[0073] For example, the dry electrode film may include a dry binder, wherein the dry binder may not be impregnated, dissolved or dispersed in a processing solvent during the process of manufacturing the dry electrode film. The dry binder may be, for example, a binder that does not include a processing solvent or does not come into contact with a processing solvent during the process of manufacturing the dry electrode film. The dry binder may be a fibrillated binder or a fibrous binder. The fibrillated binder or the fibrous binder may be used as a matrix for supporting and bonding the dry electrode active material and other components included in the dry electrode film. It can be confirmed that the fibrillated binder or the fibrous binder may have, for example, a fiber shape (e.g., in the form of fibers), such as, for example, in Figure 4 As shown in a scanning electron microscope image showing a cross section of a dry electrode film. The fibrillated binder can have an aspect ratio (e.g., the ratio of length to width in the image) of, for example, about 10 or more, about 20 or more, about 50 or more, or about 100 or more.
[0074] The dry binder may each independently include, for example, polytetrafluoroethylene (PTFE), polyvinylidene fluoride-co-hexafluoropropylene (PVDF-HFP) copolymer, polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), polyacrylonitrile (PAN), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, cellulose, polyvinyl pyrrolidone (PVP), polyethylene (PE), polypropylene (PP), ethylene-propylene-diene monomer (EPDM) rubber, sulfonated EPDM rubber, styrene-butadiene rubber (SBR), fluorine-containing rubber and / or any suitable combination thereof, but the present disclosure is not limited thereto, and any suitable binder that is generally available and / or generally used to manufacture dry electrodes may be used. For example, the dry binder may include a fluorine-based binder. The fluorine-based binder may be, for example, polytetrafluoroethylene (PTFE), polyvinylidene fluoride-co-hexafluoropropylene (PVDF-HFP) copolymer, polyvinylidene fluoride (PVDF) and / or any suitable combination thereof.
[0075] The dry binder may have a glass transition temperature (Tg) of, for example, about -30°C to about 150°C, about 15°C to about 150°C, about 15°C to about 130°C, about 50°C to about 130°C, about 100°C to about 130°C, or about 120°C to about 130°C. g The first dry binder may have a glass transition temperature (T ) of, for example, about -30°C to about 150°C, about 15°C to about 150°C, about 15°C to about 130°C, about 50°C to about 130°C, about 100°C to about 130°C, or about 120°C to about 130°C. gThe second dry binder may have a glass transition temperature (T ) of, for example, about -30°C to about 150°C, about 15°C to about 150°C, about 15°C to about 130°C, about 50°C to about 130°C, about 100°C to about 130°C, or about 120°C to about 130°C. g ). Polytetrafluoroethylene (PTFE) may have a glass transition temperature of, for example, about 120° C. to about 130° C. Since the glass transition temperature of the dry binder falls within the above range, a fibrillated binder or a fibrous binder may be more easily obtained in a dry electrode manufacturing process.
[0076] Relative to the gross weight of the dry electrode film, the amount of the dry binder can be, for example, about 0.1wt% to about 5wt%, about 0.5wt% to about 4wt%, or about 1wt% to about 3wt%. Because the dry electrode film includes a dry binder within these amounts, the dry electrode film can have improved adhesion and can maintain a relatively high energy density. Relative to the gross weight of the dry electrode film, the amount of the dry binder can be, for example, about 0.1wt% to about 5wt%, about 0.5wt% to about 4wt%, or about 1wt% to about 3wt%.
[0077] The dry electrode film may also include, for example, a conductive material. The conductive material may be, for example, a dry conductive material. The dry conductive material may be, for example, a conductive material that is not immersed, dissolved or dispersed in a processing solvent in the dry electrode film manufacturing process. The dry conductive material may be, for example, a conductive material that does not include a processing solvent or does not contact a processing solvent in the dry electrode film manufacturing process. The dry conductive material may include, for example, a carbon-based conductive material. The carbon-based conductive material may include, for example, a fibrous carbon-based material with an aspect ratio of 10 or more, a granular carbon-based material with an aspect ratio of 5 or less, and / or any suitable combination thereof. The dry conductive material may include, for example, a dry conductive material arranged in the dry electrode film.
[0078] The fibrous carbon-based material having an aspect ratio of 10 or more may be carbon fiber, carbon nanotube, carbon nanobelt, etc., but the present disclosure is not limited thereto, and any suitable carbon-based conductive material generally available and / or generally used in the art may be used.
[0079] The granular carbon-based material having an aspect ratio of 5 or less may be, for example, carbon black, acetylene black, Ketjen black, natural graphite, artificial graphite, etc., but the present disclosure is not limited thereto, and any suitable carbon-based conductive material generally available and / or generally used in the art may be used. The granular carbon-based material may have, for example, an aspect ratio of about 1 to about 5, about 1 to about 4, about 1 to about 3, or about 1 to about 2.
[0080] For example, the amount of the dry conductive material contained in the dry electrode film may be, for example, about 0.1 wt % to about 5 wt %, about 0.5 wt % to about 4 wt %, or about 1 wt % to about 3 wt % relative to the total weight of the dry electrode film. The amount of the dry conductive material contained in the dry electrode film as the electrode active material layer 120 may be, for example, about 0.1 wt % to about 5 wt %, about 0.5 wt % to about 4 wt %, or about 1 wt % to about 3 wt % relative to the total weight of the dry electrode film. If the dry electrode film includes the dry conductive material in these ranges, the conductivity of the dry electrode film may be improved, and the cycle characteristics of the lithium battery including the dry electrode film may be improved.
[0081] The dry electrode film may be free of residual processing solvent. Because the processing solvent that may not be intended for the dry electrode film is not used in the dry electrode film manufacturing process, the dry electrode film may include a dry electrode active material, a dry binder, and a dry conductive material, and may be free of residual processing solvent. The dry electrode film as the electrode active material layer 120 is manufactured in a dry process and therefore does not contain an intentionally added processing solvent. A small amount of solvent (which is not intentional) may remain in the dry electrode film as the electrode active material layer 120, but such a solvent is not an intentionally added processing solvent. Therefore, the dry electrode film as the electrode active material layer 120 can be distinguished from a wet electrode active material layer manufactured by mixing the components and the processing solvent and then drying to remove part or all of the processing solvent.
[0082] According to one or more embodiments, the inner electrode active material layer 122 may include a first dry electrode film including a first dry electrode active material and a first dry binder, and the outer electrode active material layer 121 may include a second dry electrode film including a second dry electrode active material and a second dry binder.
[0083] According to one or more embodiments, the first dry electrode active material may be the same as the second dry electrode active material. According to one or more embodiments, the first dry electrode active material may be different from the second dry electrode active material.
[0084] According to one or more embodiments, two or more electrode current collectors 110 may be arranged in the thickness direction inside the electrode active material layer 120. In one or more embodiments, two or more electrode current collectors 110 may be arranged by extending from the electrode active material layer 120 (e.g., penetrating the electrode active material layer 120). For example, the regions of two or more electrode current collectors 110 that are exposed to the outside by extending from the electrode active material layer 120 (e.g., penetrating the electrode active material layer 120) may each be connected to an electrode tab. For example, the electrode current collector 110 may include a porous structure, which increases the electrical network between the electrode active materials contained in the electrode active material layer 120, so that the internal resistance of the electrode 100 may be reduced. Therefore, a lithium battery including the electrode 100 may have improved fast charging and discharging characteristics.
[0085] For example, the porous structure may be disposed in a region located inside the electrode active material layer 120 in the electrode collector 110 , and a region exposed to the outside of the electrode active material layer 120 in the electrode collector 110 may not include the porous structure.
[0086] According to one or more embodiments, the porous structure may include a grid (eg, ordered porous) structure or a foam (eg, random porous) structure.
[0087] According to one or more embodiments, the porous structure may have a porosity of about 5 vol% to about 95 vol% (wherein the porosity is the pore volume relative to the total volume multiplied by 100%). For example, the porous structure may have a porosity of about 10 vol% to about 90 vol%, about 20 vol% to about 80 vol%, or about 30 vol% to about 70 vol%. According to one or more embodiments, the volume of the pores contained in the porous structure per unit volume may be about 10 vol% to about 90 vol% relative to the volume of the region of the current collector located inside the electrode active material layer. For example, the volume of the pores contained in the porous structure per unit volume may be about 15 vol% to about 85 vol%, or about 20 vol% to about 80 vol%. For example, if the porosity or pore size of the porous structure contained in the electrode current collector 110 falls within the above range, the electrical network between the electrode active materials contained in the electrode active material layer 120 may be further increased, and thus the internal resistance of the electrode 100 may be further reduced.
[0088] According to one or more embodiments, the material constituting the electrode current collector 110 may be a material that does not react with lithium, and any material that does not form an alloy or compound with lithium and has conductivity (e.g., a conductor) may be used. The metal substrate may be, for example, a metal or an alloy. The metal substrate may be made of, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), and / or any suitable alloy thereof.
[0089] Reference Figure 2 , the electrode current collector 110 may further include a second current collector 115 disposed between the upper electrode current collector 111 and the lower electrode current collector 112. For example, the second electrode current collector 115 may be disposed by penetrating the electrode active material layer 120 in substantially the same manner as the upper electrode current collector 111 and the lower electrode current collector 112. In one or more embodiments, the region of the upper electrode current collector 111 exposed to the outside of the electrode active material layer 120 and the region of the lower electrode current collector 112 exposed to the outside of the electrode active material layer 120 may each be electrically connected to an exposed region of the second electrode current collector 115 outside the electrode active material layer 120. For example, the exposed region of the current collector 110 including the second electrode current collector 115 outside the electrode active material layer 120 may be used as an electrode tab.
[0090] According to one or more embodiments, the second electrode current collector may not contain the above-mentioned porous structure. According to one or more embodiments, the second electrode current collector may also include the above-mentioned porous structure.
[0091] According to one or more embodiments, the electrode 100 may satisfy at least one of Condition 1 and / or Condition 2: Condition 1 In the electrode active material, a thickness of a region disposed between the second electrode current collector 115 and the upper electrode current collector 111 may be greater than a thickness of an outer electrode active material layer 121 of the electrode active material layer 120 above the upper electrode current collector 111 .
[0092] Condition 2 In the electrode active material, a thickness of a region disposed between the second electrode current collector 115 and the lower electrode current collector 112 may be greater than a thickness of an outer electrode active material layer 121 of the electrode active material layer 120 below the lower electrode current collector 112 .
[0093] For example, if the electrode 100 satisfies the above conditions, the distance between the electrode active material included in the electrode active material layer 120 and the electrode current collector 110 may be further reduced, and thus the internal resistance of the electrode 100 may be further reduced.
[0094] According to one or more embodiments, the electrode current collector 110 may be in the form of (e.g., selected from) a sheet, a foil, a film, a plate, a porous structure, a mesoporous structure, a structure containing through holes, a polygonal ring structure, a grid structure, a foam structure and / or a non-woven fabric structure, but the present disclosure is not limited thereto, and any suitable form generally available and / or commonly used in the art may be used.
[0095] Compared with the electrode current collector 110 included in the electrode of the prior art, the electrode current collector 110 may have a reduced thickness. Therefore, the electrode according to one or more embodiments may include, for example, a thin film current collector, which is different from the electrode including a thick current collector of the prior art. The electrode according to one or more embodiments adopts a thin film current collector with a reduced thickness, so the thickness of the electrode active material layer in the electrode including the thin film current collector can be relatively increased. Therefore, the energy density of the lithium battery using the above-mentioned electrode can be increased. The electrode current collector 110 (for example, each of the electrode current collectors 110) may include a metal substrate and an intermediate layer, and may have a thickness of, for example, less than 15μm, 14.5μm or less, or 14μm or less. Electrode current collector 110 (e.g., each of electrode current collectors 110) may have a thickness of, for example, 0.1 μm or more and less than 15 μm, about 1 μm to about 14.5 μm, about 2 μm to about 14 μm, about 3 μm to about 14 μm, about 5 μm to about 14 μm, or about 10 μm to about 14 μm.
[0096] The electrode current collector 110 may include, for example, a base film and a metal layer arranged on one or both sides (e.g., opposite sides) of the base film. The electrode current collector 110 may include a substrate, and the substrate may have, for example, a structure including a base film and a metal layer arranged on one or both sides (e.g., opposite sides) of the base film. The above-mentioned intermediate layer may be arranged on the metal layer in addition. The base film may include, for example, a polymer. The polymer may be, for example, a thermoplastic polymer. Examples of polymers may include polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), and / or any suitable combination thereof. Since a thermoplastic polymer is included in the base film, the base film may melt in the event of a short circuit, and thus a rapid increase in current may be prevented or reduced. The base film may be, for example, an insulator. The metal layer may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li) and / or any suitable alloy thereof. The metal layer may be disconnected in the event of an overcurrent, thereby acting as an electrochemical fuse, and thus may provide protection against a short circuit. The limiting current and peak current may be adjusted by adjusting the thickness of the metal layer. The metal layer may be plated or deposited on a substrate film. If the thickness of the metal layer is reduced, the limiting current and / or peak current of the electrode current collector 110 may be reduced, so that the stability of the lithium battery in the event of a short circuit may be improved.
[0097] A lead tab may be added to the metal layer for external connection. The lead tab may be welded to the metal layer or the metal layer / substrate film laminate by ultrasonic welding, laser welding, spot welding, etc. Since the substrate film and / or the metal layer melts during welding, the metal layer may be electrically connected to the lead tab. In order to further ensure welding between the metal layer and the lead tab, a metal chip may be added between the metal layer and the lead tab. The metal sheet may be a thin sheet of the same material as the metal of the metal layer. For example, the metal sheet may be a metal foil, a metal mesh, etc. For example, the metal sheet may be an aluminum foil, a copper foil, a stainless steel (SUS) foil, etc. By welding the lead tab after placing the metal sheet on the metal layer, the lead tab may be welded to the metal sheet / metal layer laminate or the metal sheet / metal layer / substrate film laminate.
[0098] Since the base film, the metal layer and / or the metal sheet melt during welding, the metal layer or the metal layer / metal sheet laminate can be electrically connected to the lead tab. The metal sheet and / or the lead tab can be further added to a portion of the metal layer. The base film can have a thickness of about 1 μm to about 50 μm, about 1.5 μm to about 50 μm, about 1.5 μm to about 40 μm, or about 1 μm to about 30 μm. If the base film has a thickness within the above range, the weight reduction of the electrode assembly can be more effectively achieved. For example, the base film can have a melting point of about 100°C to about 300°C, about 100°C to about 250°C, or about 100°C to about 200°C. If the melting point of the base film falls within the above range, the base film can be melted and easily joined to the lead tab in the welding process interval of the lead tab. In order to improve the adhesion between the base film and the metal layer, a surface treatment such as a corona treatment can be performed on the base film.
[0099] The metal layer may have a thickness of, for example, about 0.01 μm to about 3 μm, about 0.1 μm to about 3 μm, about 0.1 μm to about 2 μm, or about 0.1 μm to about 1 μm. If the thickness of the metal layer falls within the above range, the stability of the electrode assembly can be ensured while maintaining conductivity. The metal sheet may have a thickness of, for example, about 2 μm to about 10 μm, about 2 μm to about 7 μm, or about 4 μm to about 6 μm. If the thickness of the metal sheet falls within these ranges, the connection between the metal layer and the lead tab may be more easily performed. Because the electrode collector 110 has a structure as described above, the weight of the electrode may be reduced, and thus the energy density may be improved. The electrode collector 110 may be, for example, a positive electrode collector. The electrode collector 110 may be, for example, a negative electrode collector.
[0100] The dry electrode 100 may further include an intermediate layer disposed between the electrode active material layer 120 and one of the two or more electrode current collectors 110 .
[0101] The intermediate layer may be, for example, directly disposed on a side (e.g., one side or both sides (e.g., opposite sides)) of the electrode current collector 110. Therefore, no intermediate layer may be disposed between the electrode current collector 110 (e.g., at least one of the electrode current collectors) and the intermediate layer. The intermediate layer is disposed on one side or both sides (e.g., opposite sides) of the electrode current collector 110, and thus the adhesion between the substrate and the electrode active material layer 120 may be further improved.
[0102] The intermediate layer may have a thickness of, for example, 30% or less of the thickness of the electrode current collector 110. The intermediate layer may have a thickness of, for example, about 0.01% to about 30%, about 0.1% to about 30%, about 0.5% to about 30%, about 1% to about 25%, about 1% to about 20%, about 1% to about 15%, about 1% to about 10%, about 1% to about 5%, or about 1% to about 3% relative to the thickness of the electrode current collector 110. The intermediate layer may have a thickness of, for example, about 10nm to about 5μm, about 50nm to about 5μm, about 200nm to about 4μm, about 500nm to about 3μm, about 500nm to about 2μm, about 500nm to about 1.5μm, or about 700nm to about 1.3μm. If the thickness of the intermediate layer falls within these ranges, the adhesion between the electrode current collector 110 and the electrode active material layer 120 can be further increased, and the increase in the interface resistance can be suppressed or reduced.
[0103] The intermediate layer may include, for example, a binder. Because the intermediate layer includes the binder, the adhesion between the electrode current collector and the electrode active material layer may be further improved. The binder included in the intermediate layer may be, for example, a conductive binder or a non-conductive binder.
[0104] The conductive binder may be, for example, an ion conductive binder and / or an electron conductive binder. A binder having (eg, simultaneously having) both ion conductivity and electron conductivity may be classified as both an ion conductive binder and an electron conductive binder.
[0105] The ion conductive binder may be, for example, polystyrene sulfonate (PSS), polyvinylidene fluoride-co-hexafluoropropylene (PVDF-HFP) copolymer, polyvinyl fluoride (PVF), polyvinylidene fluoride (PVDF), poly(methyl methacrylate) (PMMA), polyethylene oxide (PEO), polyethylene glycol (PEG), polyacrylonitrile (PAN), polytetrafluoroethylene (PTFE), polyethylene dioxythiophene (PEDOT), polypyrrole (PPY), polyacrylonitrile (PAN), polyaniline, polyacetylene, etc. The ion conductive binder may include a polar functional group. The ion-conducting binder including polar functional groups may be, for example, Nafion, Aquivion, Flemion, Gore, Aciphex, Morgane ADP, sulfonated poly(ether ether ketone) (SPEEK), sulfonated poly(arylene ether ketone ketone sulfone) (SPAEKKS), sulfonated poly(arylether ketone) (SPAEK), sulfonated poly[bis(benzimidazolobenzisoquinolinone)] (SPBIBI), poly(styrene sulfonate) (PSS), 9,10-diphenylanthracene-2-sulfonate lithium (DPASLi +) etc. The electronically conductive binder may be, for example, polyacetylene, polythiophene, polypyrrole, poly(p-phenylene), poly(phenylene ethylene), poly(phenylene sulfide), polyaniline, etc. The intermediate layer may be, for example, a conductive layer comprising a conductive polymer.
[0106] The binder included in the intermediate layer may be (e.g., may be selected from) a binder, for example, included in the electrode active material layer. The intermediate layer may include substantially the same binder as the electrode active material layer. The binder included in the intermediate layer may be, for example, a fluorine-based binder. The fluorine-based binder included in the intermediate layer may be, for example, polyvinylidene fluoride (PVDF). The intermediate layer may be, for example, arranged on the electrode current collector in a dry or wet process. The intermediate layer may be, for example, a bonding layer including a binder.
[0107] The intermediate layer may further include, for example, a carbon-based conductive material. The carbon-based conductive material contained in the intermediate layer may be (for example, may be selected from) the carbon-based conductive material contained in the electrode active material layer. The intermediate layer may contain substantially the same carbon-based conductive material as the electrode active material layer. Since the carbon-based conductive material is included, the intermediate layer may be, for example, a conductive layer. The intermediate layer may be, for example, a conductive layer including a binder and a carbon-based conductive material.
[0108] The intermediate layer can be arranged on the electrode current collector in a dry method, for example, by deposition such as CVD or PVD. The intermediate layer can be arranged on the electrode current collector in a wet method, for example, by spin coating, dip coating, etc. The intermediate layer can be arranged on the electrode current collector by, for example, depositing a carbon-based conductive material on the electrode current collector. The dry-coated intermediate layer can be made of a carbon-based conductive material and may not include a binder. In one or more embodiments, the intermediate layer can be arranged on the electrode current collector 110 by, for example, applying a composition including a carbon-based conductive material, a binder and a solvent to the surface of the electrode current collector and drying. The intermediate layer can be a single-layer structure or a multilayer structure including a plurality of layers.
[0109] The lithium battery according to one or more embodiments includes a positive electrode, a negative electrode, and an electrolyte, wherein at least one of the positive electrode and / or the negative electrode may be the electrode 100. Since the lithium battery includes the electrode 100, the cycle characteristics of the lithium battery may be improved.
[0110] In one or more embodiments, one of the positive electrode and the negative electrode may be the electrode 100 described above, and the other electrode may be manufactured by a wet manufacturing method. For example, an electrode slurry comprising an electrode active material, a conductive material, a binder, and a solvent may be prepared, and the prepared electrode slurry may be applied to an electrode current collector and dried to manufacture the other electrode. The conductive material and binder included in the electrode manufactured by the wet method may be (for example, may be selected from) the conductive material and binder used in the manufacture of the above-mentioned dry electrode.
[0111] Next, a separator to be inserted between the positive electrode and the negative electrode is prepared.
[0112] The separator can be any suitable separator that is generally available and / or generally used in lithium batteries. As the separator, for example, a separator having relatively low resistance to the movement of electrolyte ions and excellent or suitable electrolyte solution moisture retention capacity can be used. The separator can be (for example, can be selected from) for example glass fiber, polyester, Teflon, polyethylene, polypropylene, polytetrafluoroethylene (PTFE) and / or any suitable combination thereof, and can be in the form of a non-woven fabric or a woven fabric. Windable separators such as polyethylene, polypropylene, etc. can be used for lithium ion batteries, and separators with excellent or suitable organic electrolyte solution impregnation capacity can be used for lithium ion polymer batteries.
[0113] The diaphragm may be manufactured by the following exemplary method, but the present disclosure is not necessarily limited to the following method and may be adjusted according to desired or required conditions.
[0114] First, a separator composition can be prepared by mixing a polymer resin, a filler, and a solvent. The separator composition can be directly applied to the top surface of the electrode and dried to form (or set) a separator. In one or more embodiments, the separator composition can be cast on a support and dried, and then the separator film peeled off from the support can be laminated on the top surface of the electrode to form (or set) a separator.
[0115] The polymer used in the manufacture of the separator is not limited, and any suitable polymer that is generally available and / or generally used in the binder of the electrode plate can be used. For example, vinylidene fluoride / hexafluoropropylene copolymer, polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethyl methacrylate and / or any suitable mixture thereof can be used.
[0116] Next, an electrolyte is prepared.
[0117] The electrolyte may be, for example, a liquid electrolyte, a solid electrolyte, a gel electrolyte, and / or any suitable combination thereof.
[0118] The electrolyte may be, for example, an organic electrolyte solution. The organic electrolyte solution may be prepared by dissolving a lithium salt in an organic solvent.
[0119] The organic solvent can be any suitable organic solvent that is generally available and / or generally used in the art. The organic solvent can be, for example, propylene carbonate, ethylene carbonate, fluoroethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, dibutyl carbonate, benzonitrile, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, γ-butyrolactone, dioxolane, 4-methyldioxolane, N,N-dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dioxane, 1,2-dimethoxyethane, cyclopentane, dichloroethane, chlorobenzene, nitrobenzene, diethylene glycol, dimethyl ether, any suitable mixture thereof, etc.
[0120] The lithium salt may be any suitable lithium salt commonly available and / or commonly used in the art. The lithium salt may be, for example, LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, LiAlO2, LiAlCl4, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (1≤x≤20, 1≤y≤20), LiCl, LiI and / or any suitable mixture thereof. The concentration of the lithium salt can be, for example, about 0.1M to about 5.0M.
[0121] The solid electrolyte may be, for example, an oxide-based solid electrolyte, a sulfide-based solid electrolyte, a polymer solid electrolyte, and / or any suitable combination thereof.
[0122] The solid electrolyte may be, for example, an oxide-based solid electrolyte. The oxide-based solid electrolyte may be (for example, selected from) Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 (0 <x<2,0≤y<3)、BaTiO3、Pb(Zr, Ti)O3(PZT)、Pb 1-x La x Zr 1- y Ti y O3 (PLZT) (0≤x<1, 0≤y<1), Pb(Mg3Nb 2 / 3 )O3-PbTiO3 (PMN-PT), HfO2, SrTiO3, SnO2, CeO2, Na2O, MgO, NiO, CaO, BaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiO2, Li3PO4, Lix Ti y (PO4)3 (0 < x < 2, 0 < y < 3), Li x Al y Ti z (PO4)3 (0 < x < 2, 0 < y < 1, 0 < z < 3), Li 1+x+y (Al, Ga) x (Ti, Ge) 2-x Si y P 3-y O 12 (0 ≤ x ≤ 1, 0 ≤ y ≤ 1), Li x La y TiO3 (0 < x < 2, 0 < y < 3), Li2O, LiOH, Li2CO3, LiAlO2, Li2O - Al2O3 - SiO2 - P2O5 - TiO2 - GeO2 and / or Li 3+x La3M2O 12 (M = Te, Nb or Zr, and x can be an integer from 1 to 10). The solid electrolyte can be prepared by, for example, a sintering method. For example, the oxide - type solid electrolyte can be (for example, selected from) Li7La3Zr2O 12 (LLZO) and / or Li 3+x La3Zr 2-a M a O 12 (M - doped LLZO, M = Ga, W, Nb, Ta or Al, and x is an integer from 1 to 10) garnet - type (or similar) solid electrolyte.
[0123] Sulfide - type solid electrolytes can include lithium sulfide, silicon sulfide, phosphorus sulfide, boron sulfide and / or any suitable combination thereof. Sulfide - type solid electrolyte particles can include Li2S, P2S5, SiS2, GeS2, B2S3 and / or any suitable combination thereof. Sulfide - type solid electrolyte particles can be Li2S or P2S5. Sulfide - type solid electrolyte particles generally have a higher lithium - ion conductivity than other inorganic compounds. For example, sulfide - type solid electrolytes can include Li2S and P2S5. If the sulfide solid electrolyte material constituting the sulfide - type solid electrolyte includes Li2S - P2S5, the mixed molar ratio of Li2S to P2S5 can be, for example, in the range of about 50:50 to about 90:10. In one or more embodiments, it is possible to use by adding Li3PO4, halogens, halogen compounds, Li 2+2x Zn 1-x GeO4 (“LISICON”, 0 ≤ x < 1), Li3+y PO 4-x N x ("LIPON", 0 < x < 4, 0 < y < 3), Li 3.25 Ge 0.25 P 0.75 S4 ("ThioLISICON"), Li2O - Al2O3 - TiO2 - P2O5 ("LATP"), etc. are prepared as sulfide solid electrolytes. Non - limiting examples of sulfide solid electrolyte materials may include: Li2S - P2S5; Li2S - P2S5 - LiX (X = halogen element); Li2S - P2S5 - Li2O, Li2S - P2S5 - Li2O - LiI, Li2S - SiS2, Li2S - SiS2 - LiI, Li2S - SiS2 - LiBr, Li2S - SiS2 - LiCl, Li2S - SiS2 - B2S3 - LiI, Li2S - SiS2 - P2S5 - LiI, Li2S - B2S3, Li2S - P2S5 - Z m S n (0 < m < 10, 0 < n < 10, Z = Ge, Zn or Ga); Li2S - GeS2, Li2S - SiS2 - Li3PO4 and / or Li2S - SiS2 - Li p MO q (0 < p < 10, 0 < q < 10, and M = P, Si, Ge, B, Al, Ga or In). In this regard, sulfide - based solid electrolyte materials can be prepared by processing the raw starting materials (e.g., Li2S, P2S5, etc.) of the sulfide - based solid electrolyte materials via a melt quenching method, a mechanical grinding method, etc. In one or more embodiments, a calcination process can be performed after the above - mentioned processing. Sulfide - based solid electrolytes can be amorphous, crystalline, or in their mixed state.
[0124] The polymer solid electrolyte may be, for example, an electrolyte containing a mixture of a lithium salt and a polymer or a polymer having an ion-conductive functional group. The polymer solid electrolyte may be, for example, a polymer electrolyte not containing a liquid electrolyte. The polymer included in the polymer solid electrolyte may include, for example, polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-co-hexafluoropropylene (PVDF-HFP) and / or poly(styrene-b-ethylene oxide) block copolymer (PS-PEO), poly(styrene-butadiene), poly(styrene-isoprene-styrene), poly(styrene-b-divinylbenzene) block copolymer, poly(styrene-ethylene oxide-styrene) block copolymer, polystyrene sulfonate (PSS), polyvinyl fluoride (PVF), poly(methyl methacrylate) (PMMA), polyethylene glycol (PEG), polyacrylonitrile (PAN), polytetrafluoroethylene (PTFE), polyethylene dioxythiophene (PEDOT), polypyrrole (PPY), polyacrylonitrile (PAN), polyaniline, polyacetylene, Nafion, Aquivion, Flemion, Gore, Aciplex, Morgane ADP, sulfonated poly(ether ether ketone) (SPEEK), sulfonated poly(arylene ether ketone ketone sulfone) (SPAEKKS), sulfonated poly(arylether ketone) (SPAEK), sulfonated poly[bis(benzimidazolobenzylisoquinolinone)] (SPBIBI), lithium 9,10-diphenylanthracene-2-sulfonate (DPASLi + ) and / or any suitable combination thereof, but the present disclosure is not limited thereto, and any suitable polymer electrolyte generally available and / or generally used in the art may be used. Any suitable lithium salt generally available and / or generally used in the art may be used. The lithium salt may be, for example, LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, LiAlO2, LiAlCl4, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (wherein, x and y are each 1 to 20), LiCl, LiI and / or any suitable mixture thereof.
[0125] The gel electrolyte is, for example, a gel polymer electrolyte. In one or more embodiments, the gel polymer electrolyte may be an electrolyte comprising a liquid electrolyte and a polymer, or an electrolyte comprising an organic solvent and a polymer having an ion-conductive functional group. The liquid electrolyte may be, for example, a mixture of an ionic liquid, a lithium salt and an organic solvent, a mixture of an ionic liquid and an organic solvent, and / or any suitable mixture of a lithium salt, an ionic liquid and an organic solvent. The polymer may be (for example, may be selected from) a polymer for a solid polymer electrolyte. The organic solvent may be (for example, may be selected from) an organic solvent for a liquid electrolyte. The lithium salt may be (for example, selected from) a lithium salt for a solid polymer electrolyte. An ionic liquid refers to a salt that is liquid at room temperature or a molten salt at room temperature, and the molten salt at room temperature has a melting point below room temperature and is composed only of ions. The ionic liquid may include, for example, one or more of the compounds (e.g., one or more selected from the compounds), the compound including: a) at least one cation (e.g., at least one cation selected from the following): ammonium cations, pyrrolidinium cations, pyridinium cations, pyrimidinium cations, imidazolium cations, piperidinium cations, pyrazolium cations, oxazolium cations, pyridazinium cations, phosphonium cations, sulfonium cations, triazolium cations and / or any suitable mixture thereof; and b) one or more anions (e.g., one or more selected from the following): BF4 - PF6 - 、AsF6 - 、SbF6 - 、AlCl4 - 、HSO4 - 、ClO4 - 、CH3SO3 - CF3CO2 - , Cl - Br - ,I - 、BF4 - 、SO4 2- CF3SO3 - 、(FSO2)2N - 、(C2F5SO2)2N - 、(C2F5SO2)(CF3SO2)N - , and / or (CF3SO2)2N - The gel polymer electrolyte may be formed by impregnating a polymer solid electrolyte with an electrolyte solution in a lithium battery. The gel electrolyte may also include inorganic particles.
[0126] Method for manufacturing electrode A method of manufacturing an electrode 100 according to one or more embodiments may be provided. The method of manufacturing the electrode 100 may include: preparing an electrode current collector 110 including a porous structure; preparing a first electrode structure by disposing an electrode active material layer 120 on a side (e.g., both sides (e.g., opposite sides)) of the electrode current collector 110; preparing two or more second electrode structures by rolling the first electrode structure; and manufacturing the electrode 100 by stacking two or more second electrode structures and then rolling them.
[0127] In one or more embodiments, the electrode active material layer 120 may be a dry electrode film.
[0128] In one or more embodiments, when the electrode 100 is manufactured by stacking two or more second electrode structures and then rolling them, the electrode 100 may be manufactured by disposing or arranging a second electrode current collector between the two or more second electrode structures and then rolling them.
[0129] The dry electrode film may be prepared by dry-mixing a dry electrode active material, a dry conductive material, and a dry binder to prepare a dry mixture; and preparing the dry electrode film by molding the dry mixture.
[0130] First, the dry electrode active material, the dry conductive material and the dry binder may be mixed in a dry process to prepare a dry mixture. For example, the dry mixture may be prepared by mixing the dry electrode active material, the dry conductive material and the dry binder.
[0131] Dry mixing refers to mixing without including a processing solvent. The processing solvent may be, for example, a solvent used to prepare an electrode slurry. The processing solvent may be, for example, water, N-methylpyrrolidone or 1-methyl-2-pyrrolidone (NMP), etc., but the present disclosure is not limited thereto, as long as it is a processing solvent used in the preparation of the electrode slurry. Dry mixing may be performed using an agitator, for example, at a temperature of about 15°C to about 65°C at a rotation speed of about 10 rpm to about 10,000 rpm. Dry mixing may be performed using an agitator for about 1 minute to about 200 minutes.
[0132] Dry mixing can be performed, for example, more than once. First, the dry electrode active material, the dry conductive material, and the dry binder can be subjected to a primary dry mixing to prepare a first dry mixture. The primary dry mixing can be performed, for example, at a temperature of about 25°C to about 65°C at a rotation speed of about 10rpm to about 2000rpm for 15 minutes or less. Subsequently, the first dry mixture can be further subjected to a secondary dry mixing to prepare a second mixture. The secondary dry mixing can be performed, for example, at a temperature of about 25°C to about 65°C at a rotation speed of about 3000rpm to about 9000rpm for about 10 minutes to about 60 minutes. A dry mixture including a fibrillated dry binder can be obtained by secondary dry mixing.
[0133] The agitator may be, for example, a kneader. The agitator may include, for example, a chamber, one or more rotating shafts arranged inside the chamber and rotating inside the chamber, and blades rotatably coupled to the rotating shaft and arranged along the longitudinal direction of the rotating shaft. The blades may be, for example, one or more of the following (e.g., selected from one or more of the following): a ribbon blade, a sigma blade, a jet (Z) blade, a dispersion blade, and / or a spiral blade. Because the blades are included, a mixture in a dough-like form can be prepared by effectively dry mixing the electrode active material, the dry conductive material, and the dry binder without using a solvent.
[0134] Examples of dry binders may include vinylidene fluoride / hexafluoropropylene copolymers, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polytetrafluoroethylene (PTFE), mixtures of the above polymers, and styrene-butadiene rubber-based polymers. The dry binder may be (eg, may be selected from) a dry binder for a dry electrode membrane.
[0135] The dry conductive material may be carbon black, graphite fine particles, natural graphite, artificial graphite, acetylene black, Ketjen black, carbon fiber, carbon nanotube, metal powder such as copper, nickel, aluminum, silver, etc., metal fiber or metal tube, conductive polymer (such as polyphenylene derivative), etc., but the present disclosure is not limited thereto, and any suitable conductive material generally available and / or generally used in the art may be used. The conductive material is, for example, a carbon-based conductive material. The dry conductive material may be (for example, may be selected from) the dry conductive material used in the above-mentioned dry electrode film.
[0136] According to one or more embodiments, a plasticizer or a pore former may be further added to the dry mixture to form (or provide) pores inside the electrode plate.
[0137] The amounts of the dry electrode active material, the dry binder, and the dry conductive material each used in the dry electrode film may be levels generally used in lithium batteries.
[0138] The dry positive electrode film may use a dry positive electrode active material as the dry active material. For the dry positive electrode active material, reference may be made to the description of the dry electrode film described above.
[0139] The dry negative electrode film may use a dry negative electrode active material as the dry electrode active material. For the dry negative electrode active material, reference may be made to the description of the dry electrode film above.
[0140] Subsequently, the dry mixture can be molded to prepare a dry electrode film.
[0141] The prepared dry mixture can be introduced into an extrusion device and extruded in the form of a sheet. The pressure during extrusion can be, for example, from about 4 MPa to about 100 MPa.
[0142] According to one or more embodiments, rolling can be performed by a roller press, a flat press, etc., but the present disclosure is not necessarily limited thereto. For example, the pressure during rolling can be about 1.0 tons / cm to about 10.0 tons / cm. For example, the temperature during rolling can be about 25°C to about 200°C.
[0143] Method for manufacturing lithium battery The lithium battery is manufactured by, for example, the following exemplary method, but the present disclosure is not necessarily limited to the following method, and the method may vary according to desired or required conditions.
[0144] First, one or both of the positive electrode and / or the negative electrode can be manufactured according to the above-mentioned method for manufacturing a dry electrode. In one or more embodiments, if one of the positive electrode and the negative electrode is manufactured by the above-mentioned method for manufacturing an electrode, the other electrode can be manufactured by a wet manufacturing method. For example, another electrode can be manufactured by preparing an electrode slurry including an electrode active material, a conductive material, a binder and a solvent, and applying the prepared electrode slurry to an electrode current collector and then drying. The conductive material and binder included in the electrode manufactured by the wet method can be (for example, selected from) the conductive material and / or binder used in the manufacture of the above-mentioned dry electrode.
[0145] Next, a separator to be inserted between the positive electrode and the negative electrode may be prepared.
[0146] The separator may be any suitable separator that is generally available and / or generally used in lithium batteries. As the separator, for example, a separator having relatively low resistance to the movement of electrolyte ions and having excellent or suitable electrolyte solution moisture retention capacity may be used. The separator may be (for example, may be selected from) for example, glass fiber, polyester, Teflon, polyethylene, polypropylene, polytetrafluoroethylene (PTFE) and / or any suitable combination thereof, and may be in the form of a nonwoven fabric or a woven fabric. Windable separators such as polyethylene, polypropylene, etc. may be used for lithium ion batteries, and separators having excellent or suitable organic electrolyte solution impregnation capacity may be used for lithium ion polymer batteries.
[0147] The diaphragm may be manufactured by the following exemplary method, but the present disclosure is not necessarily limited to the following method and may be adjusted according to desired or required conditions.
[0148] First, a separator composition can be prepared by mixing a polymer resin, a filler, and a solvent. The separator composition can be directly applied to the top surface of the electrode and dried to form (or set) a separator. In one or more embodiments, the separator composition can be cast on a support and dried, and then the separator film peeled from the support can be stacked on the top surface of the electrode to form (or set) a separator.
[0149] The polymer used in the preparation of the separator is not limited, and any suitable polymer that is generally available and / or generally used as a binder for electrode plates can be used. For example, vinylidene fluoride / hexafluoropropylene copolymer, polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethyl methacrylate and / or any suitable mixture thereof can be used.
[0150] Next, an electrolyte may be prepared. For the electrolyte, reference may be made to the description of the above lithium battery.
[0151] Reference Figure 6 , the lithium battery 1 according to one or more embodiments may include a positive electrode 3, a negative electrode 2, and a separator 4. The positive electrode 3, the negative electrode 2, and the separator 4 may be wound or folded to form (or set) a battery structure. The formed battery structure may be housed in a battery case 5. An organic electrolyte solution may be injected into the battery case 5 and sealed with a cap assembly 6 to complete the lithium battery 1. The battery case 5 may have a cylindrical shape, but the present disclosure is not necessarily limited thereto, and may have a polygonal shape, a thin film shape, etc.
[0152] Reference Figure 7, a lithium battery 1' according to one or more embodiments may include a positive electrode 3', a negative electrode 2' and a separator 4'. The separator 4' may be arranged between the positive electrode 3' and the negative electrode 2', and the positive electrode 3', the negative electrode 2' and the separator 4' may be wound or folded to form (or set) a battery structure 7'. The formed battery structure 7' may be accommodated in a battery housing 5'. An electrode tab 8' may be included that serves as an electrical path for directing the current generated in the battery structure 7' to the outside. An organic liquid electrolyte may be injected into the battery housing 5' and sealed to complete the lithium battery 1'. The battery housing 5' may have a polygonal shape, but the present disclosure is not necessarily limited thereto, for example, it may also have a cylindrical shape, a thin film shape, etc.
[0153] Reference Figure 8 , a lithium battery 1'' according to one or more embodiments includes a positive electrode 3'', a negative electrode 2'' and a separator 4''. The separator 4'' is arranged between the positive electrode 3'' and the negative electrode 2'' to form (or set) a battery structure. The battery structure 7'' is stacked in a dual-battery structure and then contained in a battery housing 5''. An electrode terminal tab 8'' serving as an electrical path for directing the current generated in the battery structure 7'' to the outside may be included. An organic liquid electrolyte may be injected into the battery shell 5'' and sealed to complete the lithium battery 1''. The battery shell 5'' may have a polygonal shape, but the present disclosure is not necessarily limited thereto, and for example, may also have a cylindrical shape, a thin film shape, etc.
[0154] Pouch type (or similar) lithium battery can correspond to Figures 6 to 8 Lithium batteries in Figures 6 to 8 The pouch-type (or quasi-) battery housing of each of the lithium batteries in the invention is used as a battery housing. The pouch-type (or quasi-) lithium battery may include at least one battery structure. The separator may be arranged between the positive electrode and the negative electrode to form (or set) the battery structure. The battery structure may be stacked in a dual-battery structure, impregnated with an organic electrolyte solution, and then contained and sealed in a bag to complete a pouch-type (or quasi-) lithium battery. For example, the positive electrode, negative electrode, and separator described above may be simply stacked so as to be contained in a bag in the form of an electrode assembly, or wound or folded into a core-type (or quasi-) electrode assembly and then contained in a bag. Subsequently, the organic electrolyte solution may be injected into the bag and sealed to complete the lithium battery.
[0155] Lithium batteries may have excellent or suitable life characteristics and relatively high rate characteristics, which makes them suitable for use in, for example, electric vehicles (EVs). For example, lithium batteries may be used in hybrid vehicles, such as plug-in hybrid electric vehicles (PHEVs), etc. In addition, lithium batteries may be used in any field that requires large amounts of energy storage. For example, lithium batteries may be used in electric bicycles, power tools, etc.
[0156] Lithium batteries can be stacked in multiples to form (or set) a battery module, and multiple battery modules can form (or set) a battery pack. Such a battery pack can be used for all types (kinds) of devices that require relatively high capacity and relatively high output. For example, the battery pack can be used in laptop computers, smart phones, electric vehicles, etc. The battery module may include, for example, multiple batteries and a frame for holding (fixing) the batteries. The battery pack may include, for example, multiple battery modules and bus bars for connecting them. The battery module and / or battery pack may also include a cooling device. Multiple battery packs can be regulated by a battery management system. The battery management system may include a battery pack and a battery control device connected to the battery pack.
[0157] The present disclosure is described in more detail with reference to the following examples and comparative examples. However, the examples are only for the purpose of illustrating embodiments of the present disclosure, and the scope of the present disclosure is not limited thereto.
[0158] Manufacturing of lithium batteries (half-cells) Example 1: With Figure 1 The structure of the electrode is the same as that of Fabrication of positive electrode film and positive electrode The average particle size (D50) of LiNi 0.91 Co 0.05 Al 0.04 O2 (hereinafter, referred to as NCA91), dry carbon-based conductive material and polytetrafluoroethylene (PTFE) as a dry binder were introduced into a blade mixer at a weight ratio of 96:2:2, and then primary dry mixing was performed at 25°C at a speed of 1200 rpm for 10 minutes to prepare a first dry mixture in which the dry positive electrode active material, the dry carbon-based conductive material and the dry binder were uniformly (substantially uniformly) mixed. As the dry carbon-based conductive material, a mixture of carbon nanotubes (CNT) and Ketjen black (ECP) at a weight ratio of 7:3 was used.
[0159] Subsequently, in order to allow fibrillation of the dry binder to proceed, the first dry mixture was subjected to additional secondary mixing at 25° C. for 25 minutes at a speed of 4000 rpm using a blade mixer to prepare a second dry mixture.
[0160] No solvent is used in the preparation of the first dry mixture and the second dry mixture.
[0161] The prepared second dry mixture was put into an extruder and extruded to prepare a dry positive electrode film in the form of a sheet of a self-standing film. The pressure during extrusion was about 60 MPa.
[0162] The prepared positive electrode film was rolled to prepare a rolled dry electrode self-supporting film. The pressure during rolling was about 3.5 tons / cm 2 The thickness of the dry positive electrode film was about 200 μm.
[0163] A thin aluminum film having a thickness of 25 μm and including a grid structure was prepared. The porosity of the thin aluminum film was 50%. A dry positive electrode film was arranged on both sides (eg, opposite sides) of the grid structure of the thin aluminum film, and the resultant was heated at 60°C at 3.5 tons / cm 2 The two second positive electrode structures were manufactured in substantially the same manner.
[0164] Thereafter, two second positive electrode structures were stacked and then heated at 60°C at 3.5 ton / cm 2 The positive electrode was prepared by rolling under pressure.
[0165] Coin Cell Battery Manufacturing A coin cell was fabricated by using the above prepared positive electrode, lithium metal as a counter electrode, a PTFE separator, and a solution as an electrolyte in which 1.3 M LiPF6 was dissolved in ethylene carbonate (EC) + ethyl methyl carbonate (EMC) + dimethyl carbonate (DMC) (3:4:3 volume ratio).
[0166] Example 2: With Figure 2 The structure of the electrode is the same as that of A positive electrode was manufactured in substantially the same manner as the positive electrode according to Example 1, except that a thin aluminum film having a thickness of 25 μm was arranged between the second positive electrode structures when stacking the two second positive electrode structures in Example 1. Thereafter, a coin cell was manufactured in substantially the same manner as in Example 1.
[0167] Comparative Example 1: Using a Metal Substrate Including a Foam Region The average particle size (D50) of LiNi 0.91 Co 0.05 Al 0.04 O2 (hereinafter, referred to as NCA91), dry carbon-based conductive material and polytetrafluoroethylene (PTFE) as a dry binder were introduced into a blade mixer at a weight ratio of 96:2:2, and then primary dry mixing was performed at 25°C at a speed of 1200 rpm for 10 minutes to prepare a first dry mixture in which the dry positive electrode active material, the dry carbon-based conductive material and the dry binder were uniformly (substantially uniformly) mixed. As the dry carbon-based conductive material, a mixture of carbon nanotubes (CNT) and Ketjen black (ECP) at a weight ratio of 7:3 was used.
[0168] Subsequently, in order to allow fibrillation of the dry binder to proceed, the first dry mixture was subjected to additional secondary mixing at 25° C. for 25 minutes at a speed of 4000 rpm using a blade mixer to prepare a second dry mixture.
[0169] No solvent is used in the preparation of the first dry mixture and the second dry mixture.
[0170] The prepared second dry mixture was injected into an extruder and extruded to prepare a dry positive electrode film in the form of a sheet of a self-standing film. The pressure during extrusion was about 60 MPa.
[0171] The prepared positive electrode film was rolled to prepare a rolled dry electrode self-supporting film. The pressure during rolling was about 3.5 tons / cm 2 The thickness of the dry positive electrode film was about 200 μm.
[0172] A thin aluminum film having a thickness of 25 μm and having a mesh region including a plurality of penetration regions was prepared. The ratio of the total area of the penetration regions to the total area of the thin aluminum film was 50%. Dry positive electrode films were arranged on both sides (e.g., opposite sides) of the mesh region of the thin aluminum film and heated at 60°C at 3.5 tons / cm 2 The resultant was rolled under a pressure of 0.1 to prepare a positive electrode.
[0173] Coin Cell Battery Manufacturing A coin cell was fabricated by using the positive electrode prepared above, lithium metal as a counter electrode, a PTFE separator, and a solution as an electrolyte in which 1.3 M LiPF6 was dissolved in ethylene carbonate (EC) + ethyl methyl carbonate (EMC) + dimethyl carbonate (DMC) (volume ratio of 3:4:3).
[0174] Evaluation Example 1: Evaluation of electrode resistance The mixture resistivity of each of the positive electrodes manufactured according to Examples 1 and 2 and Comparative Example 1 was measured using a Hioki electrode resistance meter.
[0175] Dry positive electrodes (36 hot-rolled electrode plates) manufactured according to Examples 1 and 2 and Comparative Example 1 were prepared, respectively, and current / voltage (100 μA, about 0.2 V to about 5.0 V) was applied to the prepared dry positive electrodes. The distance potential was measured for each of the dry positive electrodes using a measuring instrument probe, and the measured value was converted into resistance to measure the mixture / interface (electrode plate / substrate) resistance value. The mixture resistivity value was measured 5 or more times, and then the average value of the data after removing the minimum and maximum values was calculated as the mixture resistivity. The mixture resistivity of the positive electrodes manufactured according to Examples 1 and 2 and Comparative Example 1 was measured, and the measurement results are listed in Table 1.
[0176] Evaluation Example 2: Rapid charge and discharge characteristics evaluation at room temperature (25°C) The lithium batteries manufactured according to Examples 1 and 2 and Comparative Example 1 were charged at a constant current of 1C (e.g., C rate) at 25°C until the voltage reached 4.3V (vs. Li), and then cutoff was performed at a current of 0.05C while maintaining the voltage at 4.3V in a constant voltage mode. Subsequently, the lithium battery was discharged at a constant current of 0.1C until the voltage reached 2.8V (vs. Li) during discharge (formation cycle).
[0177] The lithium batteries after the formation cycle were each charged to 80% of the state of charge (SOC) at a relatively high rate of 1C rate at 25°C. Subsequently, the lithium battery was discharged at a constant current of 0.5C rate until the voltage reached 2.8V (vs. Li) during discharge. In addition, the maximum temperature of the lithium battery was measured by placing a temperature sensor on the top of the lithium battery.
[0178] The maximum temperature of the lithium battery during charging and discharging and the voltage at 80% SOC are listed in Table 1.
[0179] Table 1
[0180] As shown in Table 1, compared with the electrode of Comparative Example 1 including an electrode current collector including a porous structure, the electrodes according to Examples 1 and 2 including two or more electrode current collectors including a porous structure each have a reduced electrode internal resistance and can effectively suppress or reduce overvoltage and battery temperature increase during fast charging.
[0181] According to one or more examples, an electrode may include two or more electrode current collectors including a porous structure, and thus an internal resistance of the electrode may be reduced.
[0182] According to one or more examples, a lithium battery including the electrode may have reduced internal resistance, and thus may suppress or reduce overvoltage and temperature increase of the battery during rapid charging.
[0183] As used herein, the terms "substantially," "about," and similar terms are used as terms of approximation rather than as terms of degree, and are intended to account for the inherent deviations in measured or calculated values that one of ordinary skill in the art would recognize. As used herein, "substantially" includes the stated value and means within the acceptable range of deviation for a particular value as determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "substantially" can mean within one or more standard deviations, or within ±30%, ±20%, ±10%, ±5% of the stated value.
[0184] In addition, any numerical range described herein is intended to include all sub-ranges of the same numerical precision contained in the described range. For example, the range of "1.0 to 10.0" is intended to include all sub-ranges between the described minimum value 1.0 and the described maximum value 10.0 (and including the described minimum value 1.0 and the described maximum value 10.0), that is, having a minimum value equal to or greater than 1.0 and a maximum value equal to or less than 10.0, such as 2.4 to 7.6. Any maximum numerical limit described herein is intended to include all lower numerical limits contained therein, and any minimum numerical limit described in this specification is intended to include all higher numerical limits contained therein. Therefore, the applicant reserves the right to modify this specification and claims to explicitly describe any sub-ranges contained in the range explicitly described herein.
[0185] Additionally, the use of “may” when describing embodiments of the present disclosure refers to “one or more embodiments of the present disclosure.”
[0186] Portable devices, vehicles and / or batteries (e.g., battery controllers) and / or any other related devices or components according to embodiments of the present disclosure described herein may be implemented using any suitable hardware, firmware (e.g., application specific integrated circuits), software, or a combination of software, firmware, and hardware. For example, the various components of the device may be formed on an integrated circuit (IC) chip or on separate IC chips. In addition, the various components of the device may be implemented on a flexible printed circuit film, a tape carrier package (TCP), a printed circuit board (PCB), or formed on a substrate. In addition, the various components of the device may be processes or threads running on one or more processors in one or more computing devices for executing computer program instructions and interacting with other system components for performing the various functions described herein. The computer program instructions are stored in a memory, which may be implemented in a computing device using a standard memory device (such as a random access memory (RAM) as an example). The computer program instructions may also be stored in other non-temporary computer-readable media (such as CD-ROMs, flash drives, etc. as examples). In addition, those skilled in the art should recognize that the functionality of various computing devices may be combined or integrated into a single computing device, or the functionality of a particular computing device may be distributed across one or more other computing devices without departing from the scope of the embodiments of the present disclosure.
[0187] It should be understood that the embodiments described herein should be considered in a descriptive sense only, and not for limiting purposes. The description of features or aspects within each embodiment should generally be considered to be applicable to other similar features or aspects in other embodiments. Although embodiments of the present disclosure have been described, it is understood that the present disclosure should not be limited to these embodiments, but one of ordinary skill in the art can make one or more suitable changes and modifications within the spirit and scope of the present disclosure as defined by the attached claims and their equivalents.
Claims
1. An electrode, comprising: Electrode active material layer; as well as Two or more electrode current collectors are arranged along the thickness direction in the electrode active material layer, The two or more electrode current collectors include: an upper electrode current collector adjacent to a top surface of the electrode active material layer; and a lower electrode current collector adjacent to a bottom surface of the electrode active material layer. The electrode active material layer includes: an inner electrode active material layer between the upper electrode current collector and the lower electrode current collector; and an outer electrode active material layer outside the upper electrode current collector and the lower electrode current collector, and Wherein, the two or more electrode current collectors include a porous structure.
2. The electrode according to claim 1, wherein The thickness of the inner electrode active material layer is greater than the thickness of the outer electrode active material layer.
3. The electrode according to claim 1, wherein The inner electrode active material layer has a thickness of 10 μm to 190 μm, The outer electrode active material layer has a thickness of 10 μm to 190 μm, and The electrode active material layer has a total thickness of 20 micrometers to 380 micrometers.
4. The electrode according to claim 1, wherein The electrode active material layer is a dry electrode film, and The dry electrode membrane is a free-standing membrane and contains no residual processing solvent.
5. The electrode according to claim 4, wherein The dry electrode film comprises a dry electrode active material and a dry binder, The dry binder comprises a fibrillated binder, and The dry binder includes a fluorine-based binder.
6. The electrode according to claim 5, wherein The dry binder has a glass transition temperature of -30°C to 150°C, and The amount of the dry binder is 0.1 wt % to 5 wt % relative to the total weight of the dry electrode film.
7. The electrode according to claim 4, wherein The dry electrode film also includes a dry conductive material, The dry conductive material includes a carbon conductive material, The carbon-based conductive material includes a fibrous carbon-based material having an aspect ratio of 10 or more, a granular carbon-based material having an aspect ratio of 5 or less, or a combination thereof, and The amount of the dry conductive material is 0.1 wt % to 5 wt % relative to the total weight of the dry electrode film.
8. The electrode according to claim 1, wherein The inner electrode active material layer includes a first dry electrode film, the first dry electrode film includes a first electrode active material and a first dry binder, and The outer electrode active material layer includes a second dry electrode film, and the second dry electrode film includes a second dry electrode active material and a second dry binder.
9. The electrode according to claim 8, wherein The first dry electrode active material is the same as the second dry electrode active material.
10. The electrode according to claim 8, wherein The first dry electrode active material is different from the second dry electrode active material.
11. The electrode according to claim 1, wherein The porous structure includes a grid structure or a foam structure.
12. The electrode according to claim 1, wherein The porosity of the porous structure is 5 vol % to 95 vol %.
13. The electrode according to claim 1, wherein The volume of pores contained in the porous structure per unit volume is 10 vol % to 90 vol %. 14 . The electrode of claim 1 , further comprising a second electrode current collector between the upper electrode current collector and the lower electrode current collector.
15. The electrode according to claim 14, wherein The second electrode current collector does not contain a porous structure.
16. The electrode according to claim 14, wherein The thickness of the region between the second electrode current collector and the upper electrode current collector is greater than the thickness of the outer electrode active material layer above the upper electrode current collector, and / or A thickness of a region between the second electrode current collector and the lower electrode current collector is greater than a thickness of the outer electrode active material layer below the lower electrode current collector.
17. The electrode according to claim 1, wherein The two or more electrode current collectors each include a base film and a metal layer on a side of the base film, The base film includes a polymer, and the polymer includes polyethylene terephthalate, polyethylene, polypropylene, polybutylene terephthalate, polyimide or a combination thereof, and The metal layer includes indium, copper, magnesium, stainless steel, titanium, iron, cobalt, nickel, zinc, aluminum, germanium, lithium or alloys thereof.
18. The electrode according to claim 1, further comprising an intermediate layer between the electrode active material layer and one of the two or more electrode current collectors, in, The intermediate layer includes a carbon-based conductive material.
19. A lithium battery, comprising: Positive electrode; Negative electrode; as well as an electrolyte, between the positive electrode and the negative electrode, Wherein, at least one of the positive electrode and the negative electrode is the electrode according to claim 1.
20. The lithium battery according to claim 19, wherein: The electrolyte includes a liquid electrolyte, a solid electrolyte, a gel electrolyte or a combination thereof.
Citation Information
Patent Citations
Methods for Enhancing Colloidal Stability of Nanoparticles as T1 MRI Contrast Agent and T1 MRI Contrast Nanoparticles
KR1020230145275A